Interest sensitivity and volatility reductions: Cross-section evidence - F. Owen Irvine; Scott Schuh (Federal Reserve Bank of Boston, 2005)
As has been widely observed, the volatility of GDP has declined since the mid-1980s compared with prior years. One leading explanation for this decline is that monetary policy improved significantly in the later period. We utilize a cross-section of 2-digit manufacturing and trade industries to further investigate this explanation. Since a major channel through which monetary policy operates is variation in the federal funds rate, we hypothesized that industries that are more interest sensitive should have experienced larger declines in the variance of their outputs in the post-1983 period. We estimate interest-sensitivity measures for each industry from a variety of VAR models and then run cross-sectional regressions explaining industry volatility ratios as a function of their interest-sensitivity measures. These regressions reveal little evidence of a statistically significant relationship between industry volatility reductions and our measures of industry interest sensitivity. This result poses challenges for the hypothesis that improved monetary policy explains the decline in GDP volatility.
Keywords: E22; E32; E50; 330